Natural and anthropogenic influences on sterol geochemical characteristics in lake sediments and implications for using sterols as paleoenvironmental indicators - Zhang, Yongdong; Liu, Ning; Fu, Huan; Cui, He; Liu, Zhengwen (Journal of hydrology (Amsterdam), 2024)
[Display omitted] •Sterol geochemical features depend on lake natural processes and anthropogenic perturbations.•Cholesterol and total C27 sterols are enriched in the sediments of deep lakes.•Sitosterol and total C29 sterols are enriched in the sediments of shallow lakes.•Alpine lakes are characterized by an extreme dominance of sitosterol.•Cholesterol/brassicasterol ratio can be used to reconstruct historical lake nutrient changes. Sterol-based geochemical proxies are used to reconstruct the historical environmental evolution of lakes and their catchment areas. However, the reliability of these proxies remains challenging because the link between environmental drivers and sterol geochemical characteristics has not been fully assessed. In this study, the abundance and composition of sterols were determined in sediment cores from nine lakes with contrasting natural conditions and anthropogenic perturbations to establish the response pattern of sterol geochemical characteristics to environmental drivers, and the controlling mechanisms behind this phenomenon were also tentatively speculated. Our results revealed that cholesterol and total C27 sterols were consistently enriched in the sediment cores from deep lakes (Fuxian, Lugu, and Erhai). In contrast, sitosterol and total C29 sterols were consistently enriched in the sediment cores from shallow (Changdang, Taibai, Chaohu, and Liangzi) and alpine lakes (Heihai and Jiren). The variable sterol distribution can be attributed to different natural processes in these lakes. In deep lakes, the productive zooplankton, owing to the long water column, contributed to high cholesterol levels; in shallow lakes, the delivery of massive terrestrial organic matter through abundant inflowing rivers caused a large sitosterol influx. In alpine lakes, the rapid input of alpine meadows due to the dense growth of these plants on lake shores and adjacent areas resulted in the dominance of sitosterol. The significant influence of natural processes on sterol geochemical characteristics stated above implies that the lake natural background should be considered when sterol proxies were used in paleoenvironmental studies. Comparison of sterol ratios in sediments deposited in the oligotrophic and eutrophic phases of each lake revealed a marked influence of anthropogenic perturbations on sterol distribution. In particular, the cholesterol/brassicasterol ratio exhibited consistent and significant variation with nutrient enrichment in shallow or alpine lakes, but not in deep lakes, revealing the possibility of using this ratio as a nutrient indicator in the former two types of lakes.